Historical, taxonomic, and cultural patterns in scientific naming across Animalia - Kota Nojiri; Keito Inoshita; Haruto Sugeno; Takumi Taga (PLoS ONE, 2026)
Animal naming is fundamental to biological classification and scientific communication. Beyond their taxonomic function, scientific names may also reflect historical and cultural contexts. Owing to this dual role, species names have recently attracted increasing attention from historical and humanities perspectives for both their informative value and the broader patterns they may encode. To examine large-scale patterns in naming practices, we investigated temporal trends of scientific names across Animalia using automated large-language-model-based classification approaches. Our analyses revealed systematic structure in naming practices. Periods of major global disturbances coincided with marked declines in species descriptions, while advances in biological techniques were associated with shifts in dominant naming categories. Temporal trends also varied among phyla and across eras, indicating systematic differences among taxonomic communities and variation associated with authors’ estimated nationality categories. Although individual naming decisions remain diverse and classification uncertainty persists at the micro level, consistent macro-scale patterns were detectable. Together, these findings suggest that zoological nomenclature contains structured disciplinary signals and may serve as an archive for understanding long-term patterns in taxonomic practice, as well as broader historical dynamics within the biological sciences.